Intorno a Boccaccio / Boccaccio e dintorni 2018 Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 6-7 settembre 2018) - Zamponi, Stefano (Studi e saggi, 2020)
The volume 'Intorno a Boccaccio/Boccaccio e dintorni 2018' is the outcome of the international seminar held in Certaldo on September 6 and 7, 2018, promoted by the ENGB National Association (Ente Nazionale Giovanni Boccaccio) now at its fifth edition. The seminar is held annually and was born with the intent to giving voice to young scholars, who are invited to present their research, either concluded or current. The volume, alongside contributions on the Decameron, stands out for its attention towards other Latin and vulgar works by Boccaccio (Teseida, Genealogia deorum gentilium, De mulieribus claris, Epistolae) and for two contributions focused on the iconography of Decameron and Teseida.